(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
A pot experiment was conducted to evaluate the response of two chickpea varieties to water stress at the College of Agriculture campus, Hawassa University under greenhouse from January to June 2017. Three water stress levels i.e. without stress (control), vegetative water stress and seed filling water stress were assigned as main plot, chickpea varieties Habru (Kabuli type) and Mastewal (Desi type). The treatments were laid in split plot design with four replications. The results showed that water stress significantly affected all parameters studied in this experiment. The seed filling water stress resulted greater reductions in the value of all tested parameters studied compared to optimum watering and vegetative stress except number of primary branches and harvesting index, which were significantly lower under vegetative water stress. As well, the two varieties significantly differed for all observed parameters except number of nodules per plant and nodule dry weight. Days to flowering, pod maturity, number of pods per plant, number of seeds per pod and harvest index were significantly higher for Mastewal variety while, plant height, number of primary branches, number of secondary branches, dry biomass, seed yield per plant, hundred seed weight and root dry weight were greater for Habru variety. Days to flowering, plant height, seed yield per plant, hundred seed weight, number of pods per plant and harvest index were significantly affected (p<0.05) due to all two way interactions. Water management schemes that ensure to avoid especially terminal water stress could help to maintain chickpea production, which is usually grown with residual moisture by the majority of Ethiopian farmers. Given the fact that the results are obtained from a pot experiment there is a need to substantiate the findings with field experiments conducted under contrasting moisture environments. Int. J. Agril. Res. Innov. Tech. 10(1): 13-21, June 2020